Mechanistic insights of Cucumis melo L. seeds for gastrointestinal muscle spasms through calcium signaling pathway–related gene regulation networks in WGCNA and in vitro, in vivo studies. (March 2023) - Wahid, Muqeet; Saqib, Fatima; Akhtar, Saeed; Ali, Anam; Tallei, Trina Ekawati; Simal–Gandara, Jesus
Abstract: Background: In addition to the nutritional benefits of Cucumis melo L., herbalists in Pakistan and India employ seeds to treat various ailments. This study aimed to determine the regulatory role of C. melo seeds in calcium-mediated smooth muscle contraction. Methods: We identified and quantified the phytochemicals of C. melo with LC ESI–MS/MS and HPLC, then conducted in vitro and in vivo tests to confirm the involvement in smooth muscle relaxation. Then, diarrhea-predominant irritable bowel syndrome gene datasets from NCBI GEO were acquired, DEGs and WGCNA followed by functional enrichment analysis. Next, molecular docking of key genes was performed. Results: The quantification of C. melo seeds revealed concentrations of rutin, kaempferol, and quercetin were 702.38 μg/g, 686.29 μg/g, and 658.41 μg/g, respectively. In vitro experiments revealed that C. melo seeds had a dose-dependent relaxant effect for potassium chloride (80 mM)–induced spastic contraction and exhibited calcium antagonistic response in calcium dose-response curves. In in vivo studies, Cm.EtOH exhibited antidiarrheal, antiperistaltic, and antisecretory effects. The functional enrichment of WGCNA and DEGs IBS-associated pathogenic genes, including those involved in calcium-mediated signaling, MAPK cascade, and inflammatory responses. MAPK1 and PIK3CG were identified as key genes with greater binding affinity with rutin, quercitrin, and kaempferol in molecular docking. Conclusions: The bronchodilator and antidiarrheal effects of C. melo were produced by altering the regulatory genes of calcium-mediated smooth contraction. Graphical abstract: Image 1 Highlights: Rutin, kaempferol, quercetin, apigenin, and luteolin present in Cm.EtOH. Cm.EtOH exert the antispasmodic, antiperistalsis, and antidiarrheal. Cm.EtOH had calcium ion channel blocking activity. Cm.EtOH regulate the with calcium mediate smooth muscle contraction.